2018
DOI: 10.1055/s-0038-1632398
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed Facial Models in Rhinoplasty

Abstract: Digital patient photography and morphing software have become an important part of rhinoplasty over the past few decades. Presented is a novel technology incorporating 3D photography and printing to produce life-size models for use in patient evaluation and treatment. Surveys were conducted to assess patient response and were universally positive. Early surgeon experience also indicates benefit for intraoperative use. Three-dimensional printing and modeling is a new technology that has exciting applications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…With the continuous technologic innovation in plastic surgery, recent articles in the literature demonstrate that baseline and simulated 3D images can even be printed as tangible models for consultation purposes and for use as intraoperative blueprints. 17,33…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous technologic innovation in plastic surgery, recent articles in the literature demonstrate that baseline and simulated 3D images can even be printed as tangible models for consultation purposes and for use as intraoperative blueprints. 17,33…”
Section: Discussionmentioning
confidence: 99%
“…72 Studies have demonstrated how 3D printing allows the creation of accurate, patient-specific, and life-size preoperative models for patient consultation, procedure planning, and intraoperative reference in rhinoplasty. [72][73][74][75][76][77] It has been emphasized that the tactile and visual feedback provided by the models offers an exceptional representation of surgical goals and consequently improves communication and set realistic expectations. 75,77 These are useful instruments for patient counselling and surgical decision making that can help the rhinoplasty surgeon to educate patients better and better detect those at risk of being dissatisfied postoperatively.…”
Section: Need For Innovation In Rhinoplasty: Preoperative Evaluation ...mentioning
confidence: 99%
“…[72][73][74][75][76][77] It has been emphasized that the tactile and visual feedback provided by the models offers an exceptional representation of surgical goals and consequently improves communication and set realistic expectations. 75,77 These are useful instruments for patient counselling and surgical decision making that can help the rhinoplasty surgeon to educate patients better and better detect those at risk of being dissatisfied postoperatively. 78 While 3D models allow surface landmarks to be better appreciated by the patient and surgeon, very little innovation has occurred in the imaging of the underlying nasal skeleton.…”
Section: Need For Innovation In Rhinoplasty: Preoperative Evaluation ...mentioning
confidence: 99%
“…83,84 Some of these models have recently been reported in practice with patients' improved subjective attitudes toward rhinoplasty pre-and postoperatively. [84][85][86] One review in this area noted that while modeling is helpful overall, there are still challenges that exist, namely that most biologic extruding materials are not well studied and that most models assume rigid walls and cannot accurately predict nasal valve collapse. 86 Cost-benefit for these technologies is not well understood; however, given that blepharoplasties, rhinoplasties, and rhytidectomies remain the most litigious procedures for practitioners, further studies on patient satisfaction using newer technologies would be beneficial.…”
Section: Rhinoplastymentioning
confidence: 99%